ナンキョク ショウワキチ ニオケル NLC ト PMSE ノ ドウジ カンソク - 細川, 敬祐; ホソカワ, ケイスケ; 武田, 康男; タケダ, ヤスオ; 小川, 忠彦; オガワ, タダヒコ; 門倉, 昭; カドクラ, アキラ; 行松, 彰; ユキマツ, アキラ; 佐藤, 夏雄; サトウ, ナツオ; et al. (2013)
P(論文) 昭和基地における夜光雲(NLC)と極域夏季中間圏レーダーエコー(PMSE)の同時観測について報告する.2009 年2 月11 日の2000 UT から2130 UTの間,昭和基地の南側において夜光雲が目視観測された.同時に,昭和基地SuperDARN 短波レーダーが近距離レンジにおいて特徴的なエコーを観測した.このエコーは小さいドップラー速度とスペクトル幅を持ち,短波レーダーによって観測されるPMSEの特徴と調和的であるが,同じ時間帯にNLCが観測されたことから,この特徴的な近距離エコーがPMSE であることが確認された.これに加え,NLCとPMSE の空間分布は良い一致を示し,これは短波レーダーによる観測がPMSEやNLC の2 次元分布を知る上で有用なツールになることを示唆するものである. This paper reports simultaneous observations of visible noctilucent clouds (NLC) and polar mesosphere summer echoes (PMSE) at Syowa Station (69°01′S, 38°61′E) in Antarctica. During a 1.5 h interval from 2000 to 2130 UT (2300 to 0030 LT) on Feb. 11, 2009, visible NLC were observed south of Syowa Station. The oblique sounding HF radar of SuperDARN at Syowa Station simultaneously observed peculiar echoes in the closest two range gates. The echoes had a small Doppler velocity and a narrow spectral width, which are consistent with the characteristics of PMSE in the SuperDARN data. The simultaneous appearance of the visible NLC and peculiar near-range echoes observed by the HF radar suggests that the echoes were actually a signature of PMSE in the HF band. In addition, the data from the simultaneous measurements show that the spatial distributions of NLC and PMSE in the HF band were collocated with each other, which implies that oblique sounding HF radar is a useful tool for estimating the two-dimensional horizontal distribution of PMSE. departmental bulletin paper